2015
DOI: 10.1007/s11223-015-9719-y
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling and Analysis of the Tensile and Flexural Properties of a Fiber-Orientated Hybrid Nanocomposite Using Taguchi Methodology

Abstract: Îöåíåíî âëèÿíèå òðåõ íåçàâèñèìûõ ïàðàìåòðîâ (îðèåíòàöèÿ âîëîêîí, âåñîâàÿ äîëÿ íàíî-÷àñòèö ãëèíîçåìà è êðåìíåçåìà) íà ïðî÷íîñòíûå õàðàêòåðèñòèêè ãèáðèäíîãî íàíîêîìïîçèòà èç ýïîêñèäíîé ñìîëû, àðìèðîâàííîé óãëåïëàñòèêîâûìè âîëîêíàìè, ñ íàíîäîáàâêàìè ãëèíîçåìà è êðåìíåçåìà ïðè ðàñòÿaeåíèè è èçãèáå. Äëÿ ïëàíèðîâàíèÿ ýêñïåðèìåíòîâ èñïîëüçîâàëè îðòîãîíàëüíûé íàáîð ñîãëàñíî ìåòîäèêå Òàãó÷è. Äëÿ îöåíêè ôóíêöèè îòêëèêà áûëî èçãîòîâëåíî è èñïûòàíî 16 îáðàçöîâ ïðè çàïëàíèðîâàííûõ êîìáèíàöèÿõ âûøåóêàçàííûõ ïàðàìåòðîâ. Âûÿâ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This method was developed for designing experiments to investigate how various parameters affect the mean and variance of a process performance characteristic, thus define how well the 51 process is functioning. The experimental design proposed by Taguchi [26][27] used orthogonal arrays to organize the parameters affecting the process and the level at which it should be varied. It allows the collection of the necessary data to determine which factor most affect product quality with minimum amount of experimentation, and at the same manner saving time and resources.…”
Section: Experimental Procedures 21 Taguchi Methods and Variablesmentioning
confidence: 99%
“…This method was developed for designing experiments to investigate how various parameters affect the mean and variance of a process performance characteristic, thus define how well the 51 process is functioning. The experimental design proposed by Taguchi [26][27] used orthogonal arrays to organize the parameters affecting the process and the level at which it should be varied. It allows the collection of the necessary data to determine which factor most affect product quality with minimum amount of experimentation, and at the same manner saving time and resources.…”
Section: Experimental Procedures 21 Taguchi Methods and Variablesmentioning
confidence: 99%
“…Huang et al [10] suggested an increase in the tensile strength, breaking elongation, and impact strength of SiO 2 /epoxy nanocomposites at an initial silica weight fraction reaching 2 wt.%. Recent studies show that the scientific community is adopting a diversity of different methods to develop nano-reinforced composites with a varying level of success [21]. The properties of carbon nanotube (CNT)-based nanocomposites are influenced by a number of factors that include the CNT synthesis and purification process, geometrical and structural properties, their alignment in the matrix, dispersion and fabrication processes [22][23][24].…”
mentioning
confidence: 99%